Community Cookbooks in the Prairies - Kowalchuk, Kristine (Cuizine, 2013)
This article will build upon research I undertook in co-curating Culinaria: Early 20th-Century Cookbooks in the Prairies, an online exhibit beginning in late spring 2013 at the Bruce Peel Special Collections Library at the University of Alberta in Edmonton. Beginning with a personal account illustrating the real-life sharing of recipes that has occurred in the Prairies between cultural groups, this article will trace such sharing in Prairies community cookbooks. As all Prairies settlers dealt with the same relative isolation and limited ingredients, neighbours of differing ethnic groups adapted and exchanged recipes that worked in the Prairies climate. French community cookbooks contain recipes for chop suey (an influence from the Chinese restaurants in nearly every Prairie small town), German community cookbooks contain recipes for cabbage rolls, Ukrainian community cookbooks contain recipes for sauerkraut, and so on. Such sharing in fact enabled somewhat of a common culinary base unique to the Prairies: indeed chop suey, cabbage rolls, and sauerkraut appear in nearly every community cookbook, as do, for related reasons, rhubarb and saskatoon pies. Food and cookbook history in the Prairies has been little studied, presumably because the only real cookbooks published here in the first half of the twentieth century were community cookbooks (differentiating the Prairies situation from that of Ontario and Quebec), and these books largely survive only in private homes. This is gradually changing, as libraries begin to recognize the value of community cookbooks in reflecting, and contributing to, the culinary history of the Prairies.